A low cost and single source atmospheric pressure vapor phase epitaxy of ZnS for thin film photovoltaic applications - Yusoff Y.; Chelvanathan P.; Kamaruddin N.; Akhtaruzzaman M.; Amin N. (Elsevier B.V., 2023)
Atmospheric pressure; Buffer layers; Cadmium telluride; Chemical vapor deposition; Copper compounds; Gallium compounds; II-VI semiconductors; Lime; Optical emission spectroscopy; Scanning electron microscopy; Selenium compounds; Solar cells; Solar power generation; Substrates; Thin film solar cells; Tin compounds; Vapor phase epitaxy; X ray diffraction analysis; Zinc; Zinc sulfide; Chemical vapor depositions (CVD); Dry deposition process; Field emission scanning electron microscopes; Hall effect measurement; Photovoltaic; Photovoltaic applications; Soda lime glass substrate; Vapor phase reactions; Thin films